THE EFFECT OF ACCOUNTING INFORMATION SYSTEMS AND HUMAN RESOURCE COMPETENCIES ON THE QUALITY OF GOVERNMENT FINANCIAL STATEMENTS - Nurazizah, Dian; Azahra, Fatima; Jannah, Wildaniyahtul; Mahadianto, Moh. Yudi (Cirebon International Conference on Education and Economics Proceeding, 2024)
The quality of local government financial reports is measured based on normative criteria that must be fulfilled in accounting information to achieve its objectives. This study aims to explore the connection between government accounting systems and HR competencies on the preparation of regional financial reports (LKPD). An effective government financial system is the main key in ensuring transparency and accountability of public finances, Indicators of local government financial reporting are measured against four indicators in SAP: Relevant, Reliable, Comparable, and Competent. Factors such as accounting standards applied, reporting procedures, and integratin of information technology plays an important role in the integrity of the local authority financial statements (LKPD). In this study, researchers used an analytical descriptive approach to evaluate the extent to which good government accounting systems and HR competencies contribute to the quality of LKPD. The success of LKPD depends not only on compliance with regulations, but also on the ability of human resources to face complex challenges in a dynamic government environment. The findings of this conclusions poin to the Government Accounting Information System and HR competencies affect the quality of local government financial reports (LKPD). The better the implementation pertaining to accounting information systems and human resource competencies, the better the quality of government financial reports.